Modeling Hong Kong Stock Market Volatility - Mittal, Anil K.; Goyal, Niti (Indian Journal of Finance, 2011)
This article aims at studying the stock price behavior&modeling the volatility of the Hong Kong Stock Market and investigates if there is any asymmetric volatility in its return structure. It also finds out the best model for unfolding the asymmetric effects. Hang Seng Index returns have been used to proxy the Hong Kong Stock Market over the ten-year period starting from October 1st, 2000- September 30th, 2010. The return series exhibit heteroskedasticity, volatility clustering&has fat tails. GARCH (1, 1) model has been found to be the most appropriate model to capture the symmetric effects and among the asymmetric models, EGARCH (1, 1) has been found to be the best as per AIC&LL criterion. The ARCH in Mean model reported that Hong Kong market does not offer risk premium. Apart from the presence of the leverage effect, we also found very high volatility persistence over the period considered.